Synergetic paradoxes of life and education in the informational dimension - Yurzhenko, Volodymyr (Professional Pedagogics, 2018)
The use of informational resources in education encourages the use of large data bulk labeled by the term "Big Data". The present article considers the possibilities of occurrence of innovative algorithms allowing finding unknown or rather unexplored models in a data bulk. That will forever change the way of our thinking and even the idea of our capabilities. Such position is extrapolated to the examples of appearance of new approaches to solving seemingly established visions in medicine, pedagogics, and information area. The data located on the platform take into consideration both the experience of teachers on the subject and the individual possibilities and wishes of the learner (student). Using the structures of the learning platforms (including the distance learning platforms), the Big Data choose a separate individual learning path for each learner. But interacting with the learners the educational and training platform self-learn itself. From the feedback, the adaptive resources of the platforms get some training offering more and more qualified result of search to the user. And the learner gets an individualized program. Large data bulk requires a clear structuring in both vertical and horizontal subordination of the elements of the system. On the other hand, nowadays new adaptively tuned systems process even less structured or even non-structured data from social networks. The trends of synergistic perception of education examined lead to the idea of the necessity of taking into account their influence on the system of vocational education.